Criteria for Broadening the SDR Currency Basket. (Policy Papers; Policy Paper ;, 2011)
The paper explores the pros and cons of maintaining the current 'freely usable currency' criterion, and clarifies indicators for assessing it. The freely usable concept and its two key elements-currencies should be "widely used" and "widely traded"-are set out in the Articles and serve important operational purposes. A formal requirement for a currency to be freely usable was adopted for SDR valuation only in 2000, although considerations relating to this concept had been taken into account earlier. Indicators for assessing freely usable currencies were first discussed in 1977, and are updated to reflect subsequent developments in financial markets and data availability. The paper suggests as indicators for "wide use" the currency composition of foreign exchange reserves, international debt securities, and international bank liabilities; and for "wide trading" it proposes foreign exchange spot market turnover.